High Resolution Computed Tomography in Asthma - Nabil Maradny; Tariq Sinan; Omolara Roberts; Abdulaziz Muquim; Jayakrishnan B; Mousa Khadadah; Ibrahim Lasheen (Oman Medical Journal, 2012)
Objectives: High-resolution computed tomography (HRCT) can detect the structural abnormalities in asthma. This study attempts to correlate these abnormalities with clinical and pulmonary function test (PFT) data.Methods: Consecutive stable asthma patients attending Mubarak Al Kabeer Hospital, Kuwait, were subjected to HRCT during a six month period from July 2004 to December 2004, after initial evaluation and PFT.Results: Of the 28 cases, sixteen (57.120had moderate, 6 (21.420had mild and 6 (21.420had severe persistent asthma. Thirteen (46.420patients had asthma for 1 to 5 years and 12 (42.920were having asthma for >10 years. Bronchial wall thickening (57.1 bronchiectasis (28.6 mucoid impaction (17.9 mosaic attenuation (10.7 air trapping (78.620and plate like atelectasis (21.420were noted. Bronchial wall thickening (p=0.044) and bronchiectasis (p=0.063) were most prevalent in males. Ten (35.720patients exhibited mild, 9 (32.120had moderate and 3 (10.720had severe air trapping. The difference in Hounsfield units between expiratory and inspiratory slices (air trapping) when correlated with percent-predicted FEV1 in right upper (r=0.25;p=0.30), left upper (r=0.20; p=0.41), right mid (r=0.15; p=0.53), left mid (r=-0.04; p=0.60), right lower (r=0.04; p=0.86) and left lower zones (r=-0.13; p=0.58) showed no relation. The same when correlated as above with the percent predicted FEF 25-75 did not show any significant association. The presence of air trapping was compared with sex (p=0.640), nationality (p=1.000), disease duration (p=1.000) and severity of symptoms (p=0.581).Conclusion: Abnormal HRCT findings are common in asthma; however, air trapping when present was not related to the duration or severity of the illness or to the FEV1.